3D UML Heuristic Challenge - McIntosh, Paul; von Pilgrim, Jens (Electronic Communications of the EASST, 2008)
Quality of diagram layout is not restricted to just the elements of one diagram and it is also not restricted to just two dimensions. Three dimensional spaces can be used to layout multiple related diagrams to give the user of the diagram a much more comprehensive view of a software system. The 3D UML Heuristic Challenge presents a workshop session that challenges the traditional methods for layout of UML diagrams and tests 10 information visualization heuristics as a means of evaluating the quality of 3D UML diagrams.